Current status of in vivo bioanalysis of nano drug delivery systems - Tingting Wang; Di Zhang; Dong Sun; Jingkai Gu (Elsevier, 2020)
The development of nano drug delivery systems (NDDSs) provides new approaches to fighting against diseases. The NDDSs are specially designed to serve as carriers for the delivery of active pharmaceutical ingredients (APIs) to their target sites, which would certainly extend the benefit of their unique physicochemical characteristics, such as prolonged circulation time, improved targeting and avoiding of drug-resistance. Despite the remarkable progress achieved over the last three decades, the understanding of the relationships between the in vivo pharmacokinetics of NDDSs and their safety profiles is insufficient. Analysis of NDDSs is far more complicated than the monitoring of small molecular drugs in terms of structure, composition and aggregation state, whereby almost all of the conventional techniques are inadequate for accurate profiling their pharmacokinetic behavior in vivo. Herein, the advanced bioanalysis for tracing the in vivo fate of NDDSs is summarized, including liquid chromatography tandem-mass spectrometry (LC-MS/MS), Förster resonance energy transfer (FRET), aggregation-caused quenching (ACQ) fluorophore, aggregation-induced emission (AIE) fluorophores, enzyme-linked immunosorbent assay (ELISA), magnetic resonance imaging (MRI), radiolabeling, fluorescence spectroscopy, laser ablation inductively coupled plasma MS (LA-ICP-MS), and size-exclusion chromatography (SEC). Based on these technologies, a comprehensive survey of monitoring the dynamic changes of NDDSs in structure, composition and existing form in system (i.e. carrier polymers, released and encapsulated drug) with recent progress is provided. We hope that this review will be helpful in appropriate application methodology for investigating the pharmacokinetics and evaluating the efficacy and safety profiles of NDDSs.